Comprehensive pan-cancer analysis and the regulatory mechanism of AURKA, a gene associated with prognosis of ferroptosis of adrenal cortical carcinoma in the tumor micro-environment - Lu, Keqiang; Yuan, Xingxing; Zhao, Lingling; Wang, Bingyu; Zhang, Yali (Frontiers in Genetics, 2023)
Background: Primary tumor curative sexual resection is the only curative option for patients with locally or locally advanced adrenocortical carcinoma (ACC). However, overall survival remains low, and most deaths occurring within the first 2 years after surgery. The mechanism of ACC recurrence is still unclear. Therefore, more accurate prognosis-related predictive biomarkers need to be urgently explored to detect the disease status of patients after surgery. Methods: ACC gene expression profile from GEO database was downloaded to identify ACC ferroptosis-related genes by differential expression analysis and intersection. A series of bioinformatics tools and methods were used to analyze the prognostic role of ACC ferroptosis-related gene and its expression level in pan-cancer. Then we analyzed its correlation with tumor immune microenvironment, immune checkpoints, DNA repair genes and methyltransferase. Result: The DEGs detected in GEO database were intersected with ferroptosis-related genes, and 42 differential expression ferroptosis-related genes were identified. Six of these 42 genes are significantly related to the prognosis of ACC, especially AURKA. Survival analysis showed that the high expression of AURKA was significantly correlated with poor prognosis in patients with multiple cancers, and there was a significant positive correlation with Th2 cells. In addition, the expression level of AURKA was also positively correlated with tumor immune infiltration in Lung adenocarcinoma (LUAD), Liver hepatocellular carcinoma (LIHC), Sarcoma (SARC), Esophageal carcinoma (ESCA) and Stomach adenocarcinoma (STAD), and negatively correlated with immune score, matrix score and calculated score in these tumors. Further analysis of the relationship between AURKA expression and immune examination gene expression showed that AURKA could regulate the tumor immune pattern in most tumors by regulating the expression level of specific immune examination genes. Conclusions: AURKA may be an independent prognostic marker for predicting the prognosis of ACC patients. pan-cancer analysis demonstrated that AURKA may play an important role in the tumor microenvironment and tumor immunity, with its potential as a predictive biomarker for multiple cancers.